2008
DOI: 10.1021/jp711886a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Emergent Chemical Bonding in Au+−Rg Complexes (Rg = Ne, Ar, Kr, and Xe)

Abstract: Evidence is presented that there is a clear covalent component in the bonding of Au+ to Kr and Au+ to Xe, with some evidence that there may be such bonding between Au+ and Ar; for Au+ and Ne, there is no such evidence, and the bonding seems to be entirely physical. A model potential analysis shows that when all attractive inductive and dispersive terms out to R-8 are properly included in the Au+-Ne case, with an Ae(-bR) Born-Mayer repulsive term, essentially all the bonding in Au+-Ne can be rationalized by phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 41 publications
7
62
0
2
Order By: Relevance
“…Shortly afterwards, these gas-phase studies were followed by the isolation of the first gold-xenon compound in the condensed phase [72], and also triatomic XeAuF has been detected in the gas phase via microwave rotational spectroscopy [73]. Most recently, the binding patterns of AuXe + and related gold/rare-gas compounds have been analyzed in detail by Belpassi et al [74] who quantified the significant amount of charge transfer in these compounds by means of relativistic four-component calculations [75]. Also the CuXe + cation has been observed experimentally, which has a significant binding energy of D(Cu + -Xe) = 98 kJ mol −1 [76], whereas the silver analog AgXe + could not be generated under similar conditions [18,77], suggesting that D(Ag + -Xe) is much lower than D(Cu + -Xe) and D(Au + -Xe).…”
Section: Other ML + Ions With M = Cu Ag Aumentioning
confidence: 99%
“…Shortly afterwards, these gas-phase studies were followed by the isolation of the first gold-xenon compound in the condensed phase [72], and also triatomic XeAuF has been detected in the gas phase via microwave rotational spectroscopy [73]. Most recently, the binding patterns of AuXe + and related gold/rare-gas compounds have been analyzed in detail by Belpassi et al [74] who quantified the significant amount of charge transfer in these compounds by means of relativistic four-component calculations [75]. Also the CuXe + cation has been observed experimentally, which has a significant binding energy of D(Cu + -Xe) = 98 kJ mol −1 [76], whereas the silver analog AgXe + could not be generated under similar conditions [18,77], suggesting that D(Ag + -Xe) is much lower than D(Cu + -Xe) and D(Au + -Xe).…”
Section: Other ML + Ions With M = Cu Ag Aumentioning
confidence: 99%
“…Noble gas (Ng) chemistry has turned into a new and fascinating field of study since the Ng-containing compound, xenon hexafluoroplatinate [Xe þ (PtF 6 ) À ], was reported four decades ago [1]. In particular, species containing both inert noble gases and noble metal atoms have stimulated great interest.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, species containing both inert noble gases and noble metal atoms have stimulated great interest. Ng-M bonding in the complexes NgMX(Ng¼Ar, Kr, Xe; M¼Cu, Ag, Au; and X¼F, Cl, Br) has been the subject of many theoretical and experimental studies [2][3][4][5][6][7][8]. Recently, Seidel and Seppelt [9] demonstrated the existence of the [AuXe 4 ] 2þ cation in the crystal structure of AuXe 2þ 4 Sb 2 F À1 11 À Á 2 ; in the complex, Xe functions as an electron donor to Au 2þ .…”
Section: Introductionmentioning
confidence: 99%
“…Pyykko¨ [3] suggested that most of the bonding is covalent in character, but this interpretation was questioned by Read and Buckingham, who noted that 'covalency within the RgAu þ species appears to be unproven' [5]. Recent investigations [26,29] show that there is clearly a covalent component in the bonding of Xe(Kr/Ar)-Au þ . However, the heavier rare gases, xenon or krypton, have more varied chemistry than the lighter one, neon, due to their greater polarizability.…”
Section: Introductionmentioning
confidence: 99%